1995
DOI: 10.1159/000188716
|View full text |Cite|
|
Sign up to set email alerts
|

Studies in a Hemodialysis Patient Indicating that Calcitriol May Have a Direct Suppressive Effect on Bone

Abstract: Calcitriol putatively suppresses bone activity by decreasing parathyroid hormone (PTH) levels. Results of studies in a 52-year-old female maintenance hemodialysis patient suggest that calcitriol may also have a direct suppressive effect on bone. The PTH-calcium relationship was evaluated through the use of low (1 mEq/1) and high (4 mEq/1) calcium hemodialyses that were performed before the initiation of calcitriol treatment, at the end of 6 weeks of thrice-weekly intravenous calcitriol administration, and 6 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
2
6
0
1
Order By: Relevance
“…Similar results were reported by Cardinal et al (33). In maintenance hemodialysis patients, the maximal PTH value is often 10 to 20 times greater than normal (70,72,73) and sometimes even greater (74). In a study of vitamin D deficiency in dogs, maximal PTH values increased by more than five-fold as vitamin D deficiency evolved during a 2-yr period (19).…”
Section: Maximal Pthsupporting
confidence: 77%
“…Similar results were reported by Cardinal et al (33). In maintenance hemodialysis patients, the maximal PTH value is often 10 to 20 times greater than normal (70,72,73) and sometimes even greater (74). In a study of vitamin D deficiency in dogs, maximal PTH values increased by more than five-fold as vitamin D deficiency evolved during a 2-yr period (19).…”
Section: Maximal Pthsupporting
confidence: 77%
“…We generally agree with the opinion advocated by Pahl et al [1] and Ureña et al [2] that calcitriol might directly suppress bone metabolism in dialysis patients. Experimental studies have supported their assumption.…”
Section: Introductionsupporting
confidence: 92%
“…Consistent with this observation, preclinical and clinical data have suggested that cinacalcet may reduce bone turnover, tissue fibrosis, bone loss and fractures (Lien et al, 2005; Cunningham et al, 2005). Likewise, some evidence suggests that calcitriol can ameliorate osteitis fibrosa (Slatopolsky et al, 1984; Andress et al, 1989), while other clinical studies show either no or detrimental effects on bone remodeling (Costa et al, 2003; Pahl et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, preclinical (Wada et al,1998) and clinical (Lien et al, 2005; Cunningham et al, 2005) evidence suggests that calcimimetics improve bone health, including reducing the incidence of fractures. Some clinical data show that calcitriol may influence bone remodeling and ameliorate osteitis fibrosa (Slatopolsky et al, 1984; Andress et al, 1989), although other studies have shown either no or detrimental effects on bone remodeling (Costa et al, 2003; Pahl et al, 1995).…”
Section: Introductionmentioning
confidence: 99%